Population mental health, help-seeking and associated barriers following the COVID-19 pandemic: Analysis of repeated nationally representative cross-sectional surveys in Czechia - Potočár, Libor; Mladá, Karolína; Kučera, Matěj; Mohr, Pavel; Winkler, Petr; Formánek, Tomáš (Psychiatry research, 2024)
This study investigated the Czech adults' mental health following the COVID-19 pandemic and the potential influence of data collection methodology on prevalence estimates. Separately, it investigated changes in help-seeking and associated barriers. Data from representative surveys on Czech adults, conducted in November 2017 (n = 3,306), in May (n = 3,021) and November 2020 (n = 3,000), and in November and December 2022 (n = 7,311), were used. Current mental disorders were assessed by the Mini International Neuropsychiatric Interview, and the treatment gap was established in individuals scoring positively. In help-seeking individuals, encountering barriers was investigated. In 2017 and 2022, 20.02 % and 27.22 % of individuals had at least one mental disorder, respectively. The 2022 panel sampling and online and telephone interviewing estimates (34.29 % and 26.7 %) were substantially higher than those from household sampling and personal interviewing (19.9 %). Prevalence rates based on household sampling and personal interviewing were broadly consistent in 2017 and 2022. The treatment gap was around 80 % from 2017 to 2022. More than 50 % of individuals encountered structural barriers in help-seeking in 2022. This study showed that prevalence rates were still elevated in 2022, but suggests that data collection methodology influenced the estimates. Separately, the treatment gap remained consistently very high, and encountering structural barriers in help-seeking was common.
Keywords: průzkumy a dotazníky; Cross-Sectional Studies; duševní zdraví; duševní poruchy; pandemie; Mental Disorders; Adult; COVID-19; dospělí; Pandemics; Surveys and Questionnaires; Humans; Česká republika; lidé; průřezové studie; Mental Health; Czech Republic